The Correlation Between Lesson Planning and Knowledge in Order to Use TPACK in School Teachers in Makassar City - Bahri, Arsad; Jamaluddin, Asham Bin; Saparuddin, Saparuddin; Ainun, Nur Aisyah; Arifuddin, Muh (Biology Teaching and Learning, 2023)
Innovative and creative teaching methods are prioritized in 21st century education. Many teachers still do not fully utilize technology, despite the fact that it is accessible to help learning. Therefore, a framework is required for the integration of pedagogy, technology, and educational resources. Technological Pedagogical and Content Knowledge is one pertinent strategy (TPACK). An overview of the relationship between teachers at Makassar's Sekolah penggerak knowledge and their capacity to apply TPACK is the goal of this quantitative descriptive study. The following result were reached: 1) The percentage of Sekolah penggerak Teachers in Makassar who possess TPACK knowledge is 92%; 2) The percentage of Sekolah penggerak Teachers in Makassar who possess TPACK ability is 92%; 3) The percentage of Sekolah penggerak Teachers in Makassar who can develop teaching modules using the TPACK approach is 94%; and 4) There is a significant correlation between TPACK knowledge and the ability to implement the TPACK framework through the development of learning tools, with a large relationship of 0.608 x 0.591 = 0.359 with a total effect of 0.518 + 0.359 = 0.87 at a significance level of 0.047 (<0.05).Keywords: Implementation Ability, Learning Planning, Sekolah penggerak, TPACK